(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article provides an overview of effective methodologies for teaching writing in a foreign language at universities that do not specialize in linguistics. It acknowledges the distinctive challenges and opportunities inherent in this context while emphasizing the significance of writing in foreign language acquisition for supporting students’ academic and professional endeavors. The abstract explores various teaching approaches, including those centered on the writing process, genre-based instruction, and integrated skills methodologies, examining their potential impact on students’ writing proficiency and critical thinking skills. The integration of technology into writing instruction is highlighted as a valuable tool to offer students interactive and authentic writing experiences.